2021
DOI: 10.48550/arxiv.2111.11536
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Decision Theory for the Mass Measurements at the Facility for Rare Isotope Beams

Abstract: Nuclear physics facilities, like the Facility for Rare Isotope Beams (FRIB), can potentially perform many nuclear mass measurements of exotic isotopes. Each measurement comes with a particular cost, both in time and money, and thus it is important to establish which mass measurements are the most informative. In this article, we show that one can use the Kullback-Leibler divergence to determine the information gained by a mass measurement. We model the information gain obtained by nuclear mass measurements fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…where φ is an arbitrary test function. It can be shown that if equation ( 12) holds for all φ, then equation (2) must hold as well: if (H − E)|ψ has any non-zero elements, then one can immediately find a φ such that equation (12) does not hold.…”
Section: Derivationmentioning
confidence: 99%
See 2 more Smart Citations
“…where φ is an arbitrary test function. It can be shown that if equation ( 12) holds for all φ, then equation (2) must hold as well: if (H − E)|ψ has any non-zero elements, then one can immediately find a φ such that equation (12) does not hold.…”
Section: Derivationmentioning
confidence: 99%
“…To obtain a reduced-order model from equation (12) we would ideally like to map ψ → ψ and find the β that satisfy equation (12) for all φ, hence ensuring the satisfaction of equation (2). Unfortunately this would result in an over-determined system because an arbitrary φ has many more degrees of freedom than ψ. Alternatively, we can derive the Ritz subspace method by imposing that the error made by the trial eigenvector is orthogonal to the N b -dimensional subspace X spanned by X:…”
Section: Derivationmentioning
confidence: 99%
See 1 more Smart Citation
“…Nuclear physics calculations often need to be repeated many times for different values of some model parameters, for example when sampling the model space for Bayesian uncertainty quantification [1][2][3][4][5][6][7][8][9] and experimental design [10][11][12]. The computational burden can be alleviated by using emulators, or surrogate models, which accurately approximate the response of the original (i.e., high-fidelity) model but are much cheaper to evaluate.…”
Section: Introductionmentioning
confidence: 99%